Effectiveness of a training program about bio-medical waste management on the knowledge and practices of health-care professionals at a tertiary care teaching institute of North India - Sukhbir Singh; Brijender S Dhillon; Nityanand A. K Shrivastava; Bhuwan Kumar; Sudip Bhattacharya (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Training of health-care providers about the various aspects of biomedical waste (BMW) management and handling (M and H) rules can improve the safe disposal of BMW and protect the patients and public from related hazards. OBJECTIVES: Our study objective was to evaluate the existing knowledge regarding BMW management rules among selected health-care professionals and to evaluate the impact of training program on BMW management on the knowledge and practices of health-care professionals. METHODOLOGY: The training program on BMW management rules was conducted in April 2018. A total of 250 participants were trained. A structured validated questionnaire was used. The data were analyzed, and the mean score of pre- and post-test was compared by the paired-t test. RESULTS: Majority of the participants were female (83%) aged 20-30 years (56%). The majority of the participants were married (74%) and were from urban areas (74%). The mean pretest and posttest score were 14.00 and 19.94 respectively (P < 0.000). CONCLUSION: The structured training on all aspects of BMW management led to statistically significant improvement in the knowledge among health-care professionals. RECOMMENDATIONS: Such training programs need to be regularly conducted.